2017
DOI: 10.1017/s0959270916000368
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of direct payments to increase reproductive success of sandbar-nesting river birds in Cambodia

Abstract: SummaryDirect payments to communities or individuals have gained traction as a tool for species conservation; however, few studies have evaluated their effectiveness. From 2010 to 2014, we monitored nests and implemented a direct payment nest protection programme for six sandbar-nesting bird species on the Mekong River, Cambodia, and tested if nest protection improved reproductive success. Nests were guarded by community members; additionally, exclosures were used to protect nests of River Tern Sterna aurantia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…The nest survival rates of river lapwings were estimated for the first time in India, although Claassen et al. 19 have calculated nest survival rates in Cambodia. We found that nests of the river lapwing were dispersed in four habitat types, that is, open, unvegetated river bank, open, unvegetated island, vegetated river bank and crop fields.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The nest survival rates of river lapwings were estimated for the first time in India, although Claassen et al. 19 have calculated nest survival rates in Cambodia. We found that nests of the river lapwing were dispersed in four habitat types, that is, open, unvegetated river bank, open, unvegetated island, vegetated river bank and crop fields.…”
Section: Discussionmentioning
confidence: 99%
“…At each depredated nest, we recorded potential diagnostic evidence adapted from Fies and Puckett 33 including faeces, hair, the egg remains, nest disturbance and the characteristic tracks of predators such as birds and mammals on the substrate. 11,19 We adapted the approach of Sargeant et al. 34 to identify predators from egg remains.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations